Genetic databases: Socio-ethical issues in the collection and use of DNA - Tutton, Richard; Corrigan, Oonagh (Routledge, 2004)
Genetic Databases offers a timely analysis of the underlying tensions, contradictions and limitations of the current regulatory frameworks for, and policy debates about, genetic databases. Drawing on original empirical research and theoretical debates in the fields of sociology, anthropology and legal studies, the contributors to this book challenge the prevailing orthodoxy of informed consent and explore the relationship between personal privacy and the public good. They also consider the multiple meanings attached to human tissue and the role of public consultations and commercial involvement in the creation and use of genetic databases. The authors argue that policy and regulatory frameworks produce a representation of participation that is often at odds with the experiences and understandings of those taking part. The findings present a serious challenge for public policy to provide mechanisms to safeguard the welfare of individuals participating in genetic databases.